Child ego state is associated with high prevalence of repeated hospitalizations in patients with heart failure. (24th September 2015) - Yanagihara, Kiyotaka; Kinugasa, Yoshiharu; Shirota, Kinya; Inoue, Yoshiaki; Ishii, Hiroshige; Tsunoda, Fumiyo; Iwata, Masaaki; Sugihara, Shinobu; Takeda, Shinya; Hirai, Masayuki; Mimura, Asao; Kato, Masahiko; et al.
Abstract: Aims: Inadequate self‐care management is a leading cause of re‐hospitalization in patients with heart failure (HF). Psychological factors such as some ego functions interfere with self‐care behaviour modification, leading to poor outcomes in patients with several chronic diseases. However, characteristics of ego states in patients with repeated hospitalization for HF remain undefined. Methods and results: The present study enrolled 40 HF outpatients with previous history of HF hospitalization and receiving self‐care management. Patients' psychological characteristics were assessed by Patient Health Questionnaire (PHQ‐9) for screening depressive symptoms, and the Tokyo University Egogram (TEG) New Version II for analysing human behaviour based on five functional ego states; critical parent, nurturing parent, adult, free child, and adapted child (AC). Twelve patients (30.0%) had previous history of repeated (two or more) HF hospitalization. Most of them (75%) had a history of at least one or more re‐hospitalizations related to inadequate self‐care. Patients with repeated HF hospitalization had significantly lower AC score, which represents uncooperative and uncompromising behaviours, compared with those without repeated HF hospitalization ( P < 0.05). There were no significant differences in other parameters, including PHQ‐9, between the two groups. Conclusions: Low AC ego state was associated with high prevalence of repeated hospitalization in patients with HF. Assessing ego functions may be helpful to tailor educational approaches in these patients.